Comprehensive high-throughput RNA sequencing analysis reveals contamination of multiple nasopharyngeal carcinoma cell lines with HeLa cell genomes - Strong, Michael J; Baddoo, Melody; Nanbo, Asuka; Xu, Miao; Puetter, Adriane; Lin, Zhen (Journal of virology, 2014)
UNLABELLED: In an attempt to explore infectious agents associated with nasopharyngeal carcinomas (NPCs), we employed our high-throughput RNA sequencing (RNA-seq) analysis pipeline, RNA CoMPASS, to investigate the presence of ectopic organisms within a number of NPC cell lines commonly used by NPC and Epstein-Barr virus (EBV) researchers. Sequencing data sets from both CNE1 and HONE1 were found to contain reads for human papillomavirus 18 (HPV-18). Subsequent real-time reverse transcription-PCR (RT-PCR) analysis on a panel of NPC cell lines identified HPV-18 in CNE1 and HONE1 as well as three additional NPC cell lines (CNE2, AdAH, and NPC-KT). Further analysis of the chromosomal integration arrangement of HPV-18 in NPCs revealed patterns identical to those observed in HeLa cells. Clustering based on human single nucleotide variation (SNV) analysis of two separate HeLa cell lines and several NPC cell lines demonstrated two distinct clusters with CNE1, as well as HONE1 clustering with the two HeLa cell lines. In addition, duplex-PCR-based genotyping showed that CNE1, CNE2, and HONE1 do not have a HeLa cell-specific L1 retrotransposon insertion, suggesting that these three HPV-18(+) NPC lines are likely products of a somatic hybridization with HeLa cells, which is also consistent with our RNA-seq-based gene level SNV analysis. Taking all of these findings together, we conclude that a widespread HeLa contamination may exist in many NPC cell lines, and authentication of these cell lines is recommended. Finally, we provide a proof of concept for the utility of an RNA-seq-based approach for cell authentication. IMPORTANCE: Nasopharyngeal carcinoma (NPC) cell lines are important model systems for analyzing the complex life cycle and pathogenesis of Epstein-Barr virus (EBV). Using an RNA-seq-based approach, we found HeLa cell contamination in several NPC cell lines that are commonly used in the EBV and related fields. Our data support the notion that contamination resulted from somatic hybridization with HeLa cells, likely occurring at the point of cell line establishment. Given the rarity of NPCs, the long history of NPC cell lines, and the lack of rigorous cell line authentication, it is likely that the actual prevalence and impact of HeLa cell contamination on the EBV field might be greater. We therefore recommend cell line authentication prior to performing experiments using NPC cell lines to avoid inaccurate conclusions. The novel RNA-seq-based cell authentication approach reported here can serve as a comprehensive method for validating cell lines.
Keywords: Carcinoma; sekvenční analýza RNA; kontaminace DNA; Humans; HeLa buňky; Nasopharyngeal Carcinoma; nasofaryngeální karcinom; genom; Genome; lidé; karcinom; nádory nosohltanu; HeLa Cells; DNA Contamination; polymerázová řetězová reakce; Polymerase Chain Reaction; vysoce účinné nukleotidové sekvenování; nádorové buněčné linie; High-Throughput Nucleotide Sequencing; Cell Line, Tumor; Sequence Analysis, RNA; Nasopharyngeal Neoplasms